Multispecies Leisure 2021
DOI: 10.4324/9781003145677-1
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies leisure: Human-animal interactions in leisure landscapes

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law.The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team.We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Humans' perceived moral superiority over any other entity has led them to treat animals as property, resources or commodities that satisfy human interests, thereby stripping away animals' value as individuals (Fennell, 2012). Animals are usually reduced to a species-level identity and only considered if humans are affected by their actions or behaviours (Danby et al, 2019).…”
Section: Posthumanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Humans' perceived moral superiority over any other entity has led them to treat animals as property, resources or commodities that satisfy human interests, thereby stripping away animals' value as individuals (Fennell, 2012). Animals are usually reduced to a species-level identity and only considered if humans are affected by their actions or behaviours (Danby et al, 2019).…”
Section: Posthumanismmentioning
confidence: 99%
“…Leisure studies have demonstrated that human relations with horses, in particular, are more diverse, intimate, long, complex and collaborative when they serve leisure purposes (Danby et al, 2019). Nonetheless, forcing horses to perform for humans can also be regarded as a form of animal abuse.…”
Section: Horses In Leisure and Tourismmentioning
confidence: 99%
See 1 more Smart Citation